PENGGUNAAN METODE STATIS DAN LIVE FORENSIK PADA UAV UNTUK MENDAPATKAN BUKTI DIGITAL - Ibnu Fajar Arrochman; Dhomas Hatta Fudholi; Yudi Prayudi (ILKOM Jurnal Ilmiah, 2019)
In recent years, the use of drones by civilians is increasing rapidly by the presentation of total sales continued to increase rapidly every year. With the increasing possibility of Unmanned Aerial Vehicle (UAV) abuse, crime in the use of UAVs to be larger. Through forensic analysis of data using static forensic and live forensic to obtain data that allows it to be used as digital evidence. To dig up information that could be used as digital evidence in the UAV and controllers, as well as to know the characteristics of digital evidence on a UAV. The results showed that digital evidence on a UAV, the smartphone is used as a controller UAV has a very important role in the investigation. The findings in aircraft has a percentage of 50% and a camera memory card with 16.6%. DJI Phantom 3 Advanced GPS coordinates always store data in flight LOG; the data is always stored even when the flight mode is used does not use GPS signals to stability. Due to DJI Phantom 3 Advanced always use GPS on flights, file, image or video captured by the camera has the best GPS location coordinates to the metadata therein.